Case Report: Double Pectus Up in severe pectus excavatum, the new frontier of modified taulinoplasty - Frediani, Simone; Corbi, Letizia; Pardi, Valerio; Aloi, Ivan Pietro; Bertocchini, Arianna; Accinni, Antonella; Reali, Simone; Schingo, Paolo Maria Salvatore; Inserra, Alessandro (Frontiers in Pediatrics, 2024)
Introduction: Pectus excavatum, also known as "sunken chest" or "funnel chest," is a congenital condition where the sternum caves inward, creating a noticeable depression in the chest. This deformity can range from mild to severe cases, and can affect appearance and lung and heart function. Treatment options vary depending on the severity of the condition and associated symptoms. A case study was conducted on three patients suffering from severe forms of pectus excavatum using modified taulinoplasty with two Pectus Up bars. Case description: The patients were males, with an age of 15 years. Preoperatively, they underwent spirometry, an echocardiogram, and allergy tests. The procedure involved inserting two Pectus Up bars into the chest wall at the major sternal defect, allowing the implant to remain completely invisible. The procedure involved placing the sternal plate at the deepest point and anchored to the sternum with five self-tapping screws. The chest plate was then fixed to the bar using two screws. Discussion: The use of Pectus Up was first reported in 2016 and has been a subject of scientific discussion and research. The double Pectus Up technique offers improved correction, increased stability, and reduced complications. However, it also presents challenges such as increased technical complexity and potential for prolonged operative times. Patient outcomes showed promising results in terms of short-term correction and long-term stability. The use of a double bar technique in the modified Taulinoplasty procedure is a key area of ongoing clinical research and innovation in pectus excavatum repair. Further studies will be needed, including more institutions that use this technique to validate our initial experience.